Training of Trainers on Enhancing Forecasting Capacities and Crop Capability Prediction Model and Tools - Amha, Yosef; Garanganga, Bradwell; Nyakutambwa, Trymore; Kondo, Farai; Demissie, Teferi Dejene; Solomon, Dawit (Accelerating Impacts of CGIAR Climate Research for Africa, 2022)
The negative impact of hydro-meteorological hazards on the agricultural sector often leads to food insecurity. It is, therefore, incumbent upon policymakers to formulate appropriate strategies aimed at minimizing the effects of hydro-meteorological hazards on communities and economies. Hence, there is a need for timely and tailored climaterelated knowledge, information and products that support decision-making to reduce climate-related losses and enhance benefits. A series of studies have been commissioned by the ACPC-UNECA and its regional partners, such as CCAFS, under the WISER program to demonstrate the SEB of CIS in the agricultural sector. One such effort was conducting a study on Enhancing Forecasting Capacities and Developing Crop Capability Prediction Models in Malawi, Mozambique and Zimbabwe, where CIS-based DST has been developed. This DST is a critical tool to guide policymakers and communities in making science-informed decisions for optimum productivity through improved efficiencies in agricultural production systems and contributing to minimizing impacts of hydro-meteorological hazards. To operationalize this tool, however, there is a need to conduct a concerted capacity development across the SADC sub-region and beyond.